UDC 687.1.001.02:675.042 LITERARY ANALYSIS NEW TECHNOLOGIES OF WOMEN’S OUTER CLOTHING FROM CARAKUL: LITERARY ANALYSIS NEW TECHNOLOGIES OF WOMEN’S OUTER CLOTHING FROM CARAKUL - Xoliqova, Nigora; Пулатова , Сабоҳат (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
LITERARY ANALYSIS NEW TECHNOLOGIES OF WOMEN'S OUTER CLOTHING FROM CARAKUL